Visualize this: the flowingdata guide to design, visualization, and statistics - Yau, Nathan (Chichester, 2011)
"Practical data design tips from a data visualization expert of the modern age Data doesn't decrease; it is ever-increasing and can be overwhelming to organize in a way that makes sense to its intended audience."